2008
DOI: 10.1093/pcp/pcn163
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of R2R3-MYB and bHLH Transcription Factors Regulating Anthocyanin Biosynthesis in Gentian Flowers

Abstract: Gentian plants have vivid blue-colored flowers, caused by accumulation of a polyacylated anthocyanin 'gentiodelphin'. We previously performed expression analysis of gentiodelphin biosynthetic genes, and hypothesized that the white-flowered gentian cultivar 'Polarno White' might have resulted from the mutation of certain regulatory factors responsible for anthocyanin biosynthesis in flower petals. In this study, we isolated 26 R2R3-MYB gene fragments including four full-length cDNAs (GtMYB2a, GtMYB2b, GtMYB3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
108
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(111 citation statements)
references
References 47 publications
0
108
0
1
Order By: Relevance
“…Furthermore, the MYB-bHLH protein complexes involved in the regulation of flavonoid genes in Arabidopsis and also in other species such as rice (Oryza sativa), maize (Zea mays), cotton (Gossypium hirsutum), apple (Malus domestica), strawberry (Fragaria spp. ), snapdragon (Antirrhinum majus), beefsteakplant (P. frutescens), gerbera (Gerbera hybrida), and clustered gentian (Gentiana triflora; Martin et al, 1991;Grotewold et al, 2000;Hu et al, 2000;Aharoni et al, 2001;Sompornpailin et al, 2002;Elomaa et al, 2003;Humphries et al, 2005;Schwinn et al, 2006;Sweeney et al, 2006;Espley et al, 2007;Furukawa et al, 2007;Nakatsuka et al, 2008;Brueggemann et al, 2010;LinWang et al, 2010) have been rigorously characterized.…”
Section: Combinatorial Gene Regulation By Myb-bhlh Complexesmentioning
confidence: 99%
“…Furthermore, the MYB-bHLH protein complexes involved in the regulation of flavonoid genes in Arabidopsis and also in other species such as rice (Oryza sativa), maize (Zea mays), cotton (Gossypium hirsutum), apple (Malus domestica), strawberry (Fragaria spp. ), snapdragon (Antirrhinum majus), beefsteakplant (P. frutescens), gerbera (Gerbera hybrida), and clustered gentian (Gentiana triflora; Martin et al, 1991;Grotewold et al, 2000;Hu et al, 2000;Aharoni et al, 2001;Sompornpailin et al, 2002;Elomaa et al, 2003;Humphries et al, 2005;Schwinn et al, 2006;Sweeney et al, 2006;Espley et al, 2007;Furukawa et al, 2007;Nakatsuka et al, 2008;Brueggemann et al, 2010;LinWang et al, 2010) have been rigorously characterized.…”
Section: Combinatorial Gene Regulation By Myb-bhlh Complexesmentioning
confidence: 99%
“…Our own and Suntory Holdings' research groups have isolated and characterized most of the flavonoid biosynthetic genes responsible for flower pigmentation in gentian (Fujiwara et al 1998;Fukuchi-Mizutani et al 2003;Nakatsuka et al 2005aNakatsuka et al , 2008aTanaka et al 1996). In addition, we also revealed that the pigmentation of gentian flowers was regulated by two transcription factors, R2R3-MYB and basic Helix-LoopHelix (bHLH), designated GtMYB3 and GtbHLH1, respectively (Nakatsuka et al 2008b). It was demonstrated that in gentian flowers the GtMYB3/ GtbHLH1 transcription factor complex regulated the expressions of anthocyanin biosynthetic genes (Nakatsuka et al 2008b).…”
mentioning
confidence: 79%
“…In addition, we also revealed that the pigmentation of gentian flowers was regulated by two transcription factors, R2R3-MYB and basic Helix-LoopHelix (bHLH), designated GtMYB3 and GtbHLH1, respectively (Nakatsuka et al 2008b). It was demonstrated that in gentian flowers the GtMYB3/ GtbHLH1 transcription factor complex regulated the expressions of anthocyanin biosynthetic genes (Nakatsuka et al 2008b). …”
mentioning
confidence: 98%
“…On the other hand, G. triflora WDR ortholog 1 (GtWDR1) is expressed throughout the entire plant (our unpublished data). A yeast two-hybrid analysis has actually confirmed a protein-protein interaction between GtMYB3 and GtbHLH1, while a transient expression assay has demonstrated that cotransformation of GtMYB3 and GtbHLH1 can enhance the promoter activities of the late anthocyanin biosynthetic genes GtA5/3′AT and GtF3′5′H (Nakatsuka et al 2008a). In addition, the white-flowered cultivar 'Polarno-White' has been characterized as a GtMYB3-deficient mutant derived from the insertion of a transposable element into the coding region of the GtMYB3 gene.…”
Section: Transcription Factors Responsible For Anthocyanin Biosynthesmentioning
confidence: 96%
“…In gentian, temporal expressions of GtMYB3 and GtbHLH1 are well correlated with those of late biosynthetic genes (Nakatsuka et al 2008a). On the other hand, G. triflora WDR ortholog 1 (GtWDR1) is expressed throughout the entire plant (our unpublished data).…”
Section: Transcription Factors Responsible For Anthocyanin Biosynthesmentioning
confidence: 99%